Investigating the Resistance Properties of Concrete Containing Waste Carpet Fibers - Nejati, Faezeh; Mahboobi, Ali (Makara Journal of Technology, 2023)
This research was conducted with the aim of investigating the use of waste carpet fiber (WCF) and assessing the resistance properties of concrete. The main goal of this study was to investigate the effect of the internal processing of concrete containing WCF on increasing its resistance properties. At the same time, the secondary goals pursued in the research included determining the optimal percentages of carpet fibers in improving compressive strength, tensile strength, and bending strength. The materials used included cement, aggregates, water, WCF, and super lubricant. This research applied seven mixing designs: A, B1, B2, C1, C2, D1, and D2. Mixing plan A was the control plan. Sample B1 contained 2.45 kg/m3 of WCF and 40 kg/m3 of lyca for processing, while sample B2 contained 2.45 kg/m3 of WCF and no lyca. Sample C1 contained 35.7 kg/m3 of WCF and 80 kg/m3 of lyca for processing, sample C2 contained 35.7 kg/m3 of WCF and no lyca, Sample D1 contained 12.25 kg/m3 of WCF and 120 kg/m3 of lyca for processing, and sample D2 contained 12.25 kg/m3 of WCF and no lyca. The results showed that the use of waste carpet fibers and processing by lyca reduced the compressive strength of the samples. The results of the tensile strength test revealed that the use of waste carpet fibers along with processing by lyca increased the tensile strength of the samples. Finally, the flexural strength test results showed that the use of small amounts of WCF and lyca treatment led to an increase in the flexural strength of concrete.